Multiresistant Fusarium Pathogens on Plants and Humans: Solutions in (from) the Antifungal Pipeline? - Al-Hatmi AMS; de Hoog GS; Meis JF (Infection and Drug Resistance, 2019)
Abdullah MS Al-Hatmi,1–3 G Sybren de Hoog,2,3 Jacques F Meis3,4 1Ministry of Health, Directorate General of Health Services, Ibri, Oman; 2Westerdijk Fungal Biodiversity Institute, Utrecht, the Netherlands; 3Centre of Expertise in Mycology Radboud University Medical Centre/Canisius Wilhelmina Hospital, Nijmegen, the Netherlands; 4Department of Medical Microbiology and Infectious Diseases, Canisius Wilhelmina Hospital, Nijmegen, the NetherlandsCorrespondence: Abdullah MS Al-HatmiDirectorate General of Health Services, PO Box 46, 516 Al-Akdhar, Ibri, OmanTel +968 25691905Fax +968 25691915Email abdullaalhatmi@gmail.comAbstract: The fungal genus Fusarium contains numerous plant pathogens causing considerable economic losses. In addition, Fusarium species are emerging as opportunistic human pathogens causing both superficial and systemic infections. Appropriate treatment of Fusarium infections in a clinical setting of neutropenia is currently not available. ESCMID and ECMM joint guidelines, following the majority of published studies, suggest early therapy with amphotericin B and voriconazole, in conjunction with surgical debridement and reversal of immunosuppression. In this review, we elaborate on the trans-kingdom pathogenicity of Fusarium. Intrinsic resistance to several antifungal drugs and the evolution of antifungal resistance over the years are highlighted. Recent studies present novel compounds that are effective against some pathogenic fungi including Fusarium. We discuss the robust and dynamic antifungal pipeline, including results from clinical trials as well as preclinical data that might appear beneficial for patients with invasive fusariosis.Keywords: Fusarium, trans-kingdom, novel compounds, antifungal pipeline, E1210, SCY-078, ASP2397, MGCD290, olorofim, AR-12, isavuconazole, efinaconazole, luliconazole